Not another type of potato: MC1R and the russet coloration of Burmese cats. (27th September 2016) - Gustafson, N. A.; Gandolfi, B.; Lyons, L. A.
Summary: The Burmese is a breed of domestic cat that originated in Southeast Asia and was further developed in the United States. Variants in melanocortin 1 receptor ( MC1R ) causes common coat colour phenotypes in a variety of mammalian species but only limited colour variation in the domestic cat. Known as the extension ( E ) locus, melanocortin 1 receptor ( MC1R) interacts with the agouti locus to produce the eumelanin and pheomelanin pigments. Recently, a novel reddish coloration, which is termed russet, was identified in the Burmese cat breed. Because this russet Burmese coloration changes with aging, MC1R was suggested as candidate gene. The similar colouration in specific lineages of Norwegian Forest cat known as amber ( e ) (c.250G>A; p.Asp84Asn) was excluded for this Burmese phenotype. The complete 954‐bp coding region of MC1R was directly sequenced in russet Burmese and suspected carriers. A 3‐bp deletion (c.439_441del) associated with the deletion of a phenyalanine (p.Phe146del) in the protein sequence was identified. All russet coloured cats were homozygous for the variant, and all obligate carriers were heterozygous, confirming that the deletion segregated concordantly with colouring in Burmese cats from the New Zealand foundation lineage. The variant was not identified in 442 cats from 26 different breeds and random‐bred cats. Twenty‐six Burmese from the USA did not have the variant. This MC1R variant defines a unique coloration and the second breed‐specific MC1R variant in cats. The interactions of the two recessive feline MC1R alleles ( E  >  e, e r ) is unknown.